A review on formation, characterization, and role of micro/nanotextured surfaces on boiling heat transfer performance - Kumar N.; Ghosh P.; Shukla P. (My University, 2025)
In the present study, we investigate high-energy density devices, which need efficient cooling mechanisms for continuous operation. In the last two decades many studies have been conducted to examine the role of micro/nanostructured surfaces on pool boiling performance. Most studies have revealed that surface modifications significantly improve the boiling phenomena. In that context, many researchers have investigated boiling phenomena in relation to various types of prepared structures. In this paper, we discuss various types of micro/nanostructured preparations and their characterization techniques. The preparation techniques are classified as thin film deposition, lithography, and etching. We mainly focus on three recent trends of micro/nanostructured surfaces known as nanowire, nanoporous, and hybrid surfaces. The effects of all of these structured surfaces on the boiling heat transfer rate and critical heat flux are included and reviewed closely in relation to pool boiling. Finally, we conclude the paper with a broad summary of the important features and challenges of using micro/nanostructured surfaces in real applications. © 2021 by Begell House, Inc. www.begellhouse.com